Transformasi Digital Dalam Administrasi Publik: Dampaknya Terhadap Pelayanan Publik Di Bidang Ekonomi - Inne Miftah Dewi; Wiga Ayu Desamanita; Abdurrahman Arif (Universitas Mbojo Bima, 2026)
Digital transformation in public administration has become a strategic agenda for improving the quality of public services, particularly in the economic sector. However, its implementation in Indonesia still faces several challenges, including the digital divide, limited technological infrastructure, and insufficient human resource capacity and digital literacy. This study aims to analyze the impact of digital transformation in public administration on public service delivery in the economic sector and to identify the factors influencing its effectiveness. This research employs a qualitative approach using a literature review method by examining relevant national and international scholarly sources. The findings indicate that digital transformation contributes to improving service efficiency, enhancing transparency and accountability, and expanding public access to services. In addition, digitalization plays a role in creating public value through increased ease of doing business and economic activities. However, these benefits are not evenly distributed due to disparities in digital access and institutional capacity. This study concludes that the success of digital transformation in public administration depends on infrastructure readiness, human resource capacity, and the integration of sustainable policies